Computational thinking in secondary school students in Ibero-America. A systematic review from 2012 to 2022 (Revista Innova Educación, 2023)
The objective of this work was to conduct a systematic review of empirical publications on digital competence called computational thinking in secondary school students in Ibero-America in the period from 2012 to 2022. For this systematic review, articles were collected during the last 10 years, using open access databases such as: Google Scholar, Redalyc, Scielo. Additionally, closed access academic databases were used, such as: EBSCO, Springer and JSTOR. Eighteen articles were subjected to inclusion and exclusion criteria. It was found that most of the studies have been conducted in Spain and among the main results were that the teaching of this skill is essential to train students skilled in the field of technology, which in turn can improve their ability to solve problems. One aspect that stands out in this review is the boom of publications in the Iberian Peninsula and the diversity of topics addressed by the authors: problem solving through digital literacy and integration into the curriculum as a subject at the secondary level.
Keywords: students; secondary education; computational thinking; problem solving